Saharan dust inputs to the Northeast Atlantic - Gelado-Caballero, M. D. (2015)
Mineral aerosol inputs to the Canary Current Large Marine Ecosystem (CCLME) are among the highest in the world, due to its proximity to the Sahara and Sahel deserts in Africa. North Africa accounts for approximately 55% of global dust emissions. An annual average deposition resulting from different models for the Northeast Atlantic ranges between 140 Tg yr‐1 and 276 Tg yr‐1. Aerosol deposition is an important source of essential and limiting nutrients and trace metals (Fe, Co, Mn, Cu and Al) to the ocean, which may stimulate the autotrophic components (nitrogen fixation and diatoms). The impact of dust inputs on oceanic carbon uptake and climate is dependent on total dust deposition fluxes as well as the bioavailability of nutrients and metals in the dust. However, dust deposition measurements are very scarce in the CCLME region and there are very few sets of long‐term measurements of aerosol concentrations, although such data is invaluable in quantifying atmospheric inputs to this important region. Moreover, these measurements are critical for constraining climate and biogeochemical models in the CCLME region, especially because the land use and the climate change could be increasing dust emissions from the African sources.